Salivary levels of eluents during Invisalign™ treatment with attachments: an in vivo investigation - Larissa Stocker; Sevasti-Kiriaki Zervou; Spyridon N. Papageorgiou; Stephania Karakousoglou; Theodoros Triantis; Anastasia Hiskia; George Eliades; Theodore Eliades (SpringerOpen, 2024)
Abstract Background The aim of the present study was to investigate qualitatively and quantitatively the elution of substances from polyester-urethane (Invisalign™) aligners and resin composite attachments (Tetric EvoFlow) in vivo. Methods Patients (n = 11) treated with the aligners and attachments (16 per patient, without other composite restorations) for an average of 20 months, who were planned for attachment removed were enrolled in the study. Patients were instructed to rinse with 50 mL of distilled water upon entry and the rinsing solution was collected (before removal). Then, the attachments were removed with low-speed tungsten carbide burs for adhesive residue removal, a thorough water rinsing was performed immediately after the grinding process to discard grinding particle residues, and subsequently, after a second water-rinsing the solution was collected for analysis (after removal). The rinsing solutions were analyzed for targeted (LC-MS/MS: Bis-GMA, DCDMA, UDMA, BPA) and untargeted (LC-HRMS: screening of leached species and their degradation products) compounds. Results Targeted analysis revealed a significant reduction in BPA after attachment removal (4 times lower). Bis-GMA, DCDMA, UDMA were below the detection limit before removal but were all detectable after removal with Bis-GMA and UDMA at quantifiable levels. Untargeted analysis reviled the presence of mono-methacrylate transformation products of Bis-GMA (Bis-GMA-M1) and UDMA (UDMA-M1), UDMA without methacrylate moieties (UDMA-M2), and 4-(dimethylamino) benzoic acid (DMAB), the degradation product of the photo-initiator ethyl-4-(dimethylamino) benzoate (EDMAB), all after attachment removal. Several amino acids and endogenous metabolites were also found both before and after removal. Conclusions Elevated levels of BPA were traced instantaneously in patients treated with Invisalign™ and flowable resin composite attachments for the testing period. BPA was reduced after attachment removal, but residual monomers and resin degradation products were found after removal. Alternative resin formulations and attachment materials may be utilized to reduce eluents.